PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN TRANSPORTASI ONLINE GOJEK MOTOR (GORIDE) DI JAKARTA - Tukirin; Adillah Auliana (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the effect of service quality and brand image on customer satisfaction among users of Gojek Motor (GoRide) in Jakarta. The research seeks to identify how service attributes and brand perception influence customer responses and contribute to the sustainability of online transportation services. This study employs a quantitative approach with a causal associative method. Data were collected from 110 respondents through questionnaires distributed using accidental sampling. The data were analyzed using multiple linear regression techniques with the assistance of SPSS version 25. The model was tested through classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, and the results confirmed that all assumptions were fulfilled, indicating that the regression model used in this study was feasible and valid. The findings reveal that both service quality and brand image have a positive and significant effect on customer satisfaction, either partially or simultaneously. The regression equation obtained is Ŷ = −0.197 + 0.478X₁ + 0.578X₂, with a coefficient of determination (R²) of 0.824, meaning that 82.4% of customer satisfaction is explained by these two variables. This result highlights that maintaining excellent service quality and a strong brand image can enhance customer satisfaction and loyalty toward GoRide.